Cerebral and Muscle Oxygenation During Intermittent Hypoxia Exposure in Healthy Humans. Issue 6 (1st June 2016) - Rupp, Thomas; Peyrard, Arthur; Tamisier, Renaud; Pepin, Jean-Louis; Verges, Samuel
Abstract: Study Objectives: To evaluate changes in muscle and cerebral oxygenation during intermittent hypoxia (IH). Methods: Fifteen healthy subjects were exposed to 45-min IH (2-min cycles). Arterial blood oxygen saturation (SpO2), prefrontal cortex and brachial biceps muscle oxygenation (assessed by near-infrared spectroscopy), heart rate, and ventilation were continuously recorded. Results: During 2-min IH cycles, changes in SpO2 (9.2% ± 3.3%) were associated with significant changes in cortex oxygenation (3.2% ± 1.8%), minute ventilation, and heart rate, but no change in muscle oxygenation (0.2% ± 1.0%). Conclusions: Fluctuations of blood oxygen levels comparable to severe obstructive sleep apnea translate into distinct pattern of oxygenation changes in the muscle and cortex. Significance: While the consequences of sleep apnea in terms of oxygenation are generally described at the arterial blood level (i.e. intermittent hypoxemia), data from animal models suggest that changes in oxygenation may differ between tissues. In a model of intermittent hypoxia in healthy humans, the present study demonstrates that intermittent arterial hypoxemia translates into significant oscillations in cerebral oxygenation but no significant change in muscle oxygenation. These data emphasize differences between organs regarding changes in oxygenation during intermittent hypoxemia and indicate that some tissues such as the brain may be specifically vulnerable to intermittent hypoxemia. This should be taken into account when considering the pathophysiological consequences of sleep apnea.